The Influence of Fiscal Policy of Local Government Towards the Level Of Community Welfare: Exhibition Of Caresidenan Surakarta And DIY - Ahmad Amin; Intan Amandita (The Indonesian Journal of Accounting Research, 2015)
Abstract: This study aimed to examine the effect of local government fiscal policy on the public welfare in districts surrounding Surakarta and Yogyakarta. Operationalization of fiscal policy conducted using a measure of a degree of autonomy, revenue effectiveness, government activity, revenue growth, and efficiency, while public welfare was measured using the Human Development Index (HDI). The examination was done using multiple linear regression analysis. The results show that, together, a degree of autonomy, revenue effectiveness, government activity, revenue growth, and efficiency influence the achievement of HDI. However, measured individually, the only degree of autonomy and efficiency influence the achievement of HDI. Thus, it can be concluded that the government's fiscal policy affects the level of welfare. Further research should measure the difference between the achievements of the public welfare and variables affecting the health of District / Town surrounding of Surakarta and in the Province of DIYAbstrak: Penelitian ini bertujuan untuk menguji pengaruh kebijakan fiskal pemerintah daerah terhadap kesejahteraan masyarakat di kabupaten sekitar Surakarta dan Yogyakarta. Operasionalisasi kebijakan fiskal dilakukan dengan menggunakan ukuran tingkat otonomi, efektivitas pendapatan, aktivitas pemerintah, pertumbuhan pendapatan, dan efisiensi, sementara kesejahteraan masyarakat diukur dengan menggunakan Indeks Pembangunan Manusia (IPM). Pemeriksaan dilakukan menggunakan analisis regresi linier berganda. Hasilnya menunjukkan bahwa, bersama-sama, tingkat otonomi, efektivitas pendapatan, aktivitas pemerintah, pertumbuhan pendapatan, dan efisiensi mempengaruhi pencapaian IPM. Namun, diukur secara individual, hanya tingkat otonomi dan efisiensi yang mempengaruhi pencapaian IPM. Dengan demikian, dapat disimpulkan bahwa kebijakan fiskal pemerintah mempengaruhi tingkat kesejahteraan. Penelitian lebih lanjut harus mengukur perbedaan antara pencapaian kesejahteraan masyarakat dan variabel yang mempengaruhi kesejahteraan Kabupaten/Kota di sekitar Surakarta dan di Provinsi DIY